Upper Airway Stimulation for OSA: Early Adherence and Outcome Results of One Center. (15th March 2016) - Kent, David T.; Lee, Jake J.; Strollo, Patrick J.; Soose, Ryan J.
Abstract : Objective: To review outcome measures and objective adherence data for patients treated with hypoglossal nerve stimulation (HNS) therapy for moderate to severe obstructive sleep apnea (OSA). Study Design: Case series with chart review. Setting: Academic sleep medicine center. Subjects and Methods: The first 20 implanted patients to complete postoperative sleep laboratory testing were assessed. All patients had moderate to severe OSA, were unable to adhere to positive pressure therapy, and met previously published inclusion criteria for the commercially available implantable HNS system. Data included demographics, body mass index (BMI), apnea‐hypopnea index (AHI), Epworth Sleepiness Score (ESS), nightly hours of device usage, and procedure‐ and therapy‐related complications. Results: Mean age was 64.8 ± 12.0 years, with 50% female. Mean BMI was unchanged postoperatively (26.5 ± 4.2 to 26.8 ± 4.5 kg/m 2 ; P >. 05). Mean AHI (33.3 ± 13.0 to 5.1 ± 4.3; P <. 0001) and mean ESS (10.3 ± 5.2 to 6.0 ± 4.4; P <. 01) decreased significantly. Seventy percent (14/20) of patients achieved a treatment AHI <5, 85% (17/20) an AHI <10, and 95% (19/20) an AHI <15. Average stimulation amplitude was 1.89 ± 0.50 V after titration. Adherence monitoring via device interrogation showed high rates of voluntary device use (mean 7.0 ± 2.2 h/night). Conclusion: For a clinical and anatomical subset of patients with OSA, HNS therapy is associated with good objective adherence, low morbidity, and improved OSA outcome measures. Early results at one institution suggest that HNS therapy can be implemented successfully into routine clinical practice, outside of a trial setting.